Gender dynamics in value chains - Pyburn, Rhiannon; Stoian, Dietmar; Quintero, Sandra (2021)
Over the past 20 years, value chain development (VCD) initiatives and value chain research have increasingly integrated gender dimensions to allow for gender-differentiated employment and income opportunities and other benefits for women and men, and to address the exploitation of women’s labor (Pyburn and Kruijssen 2021). This research often addresses constraints to women’s participation in specific value chains, such as administrative procedures in transboundary fish trade (Ratner et al. 2018) or disproportionate harassment of women food traders by authorities in Nigeria (Resnick et al. 2019). This brief draws on research conducted under the CGIAR Research Program on Policies, Institutions, and Markets (PIM) to illustrate how VCD supports and constrains progress toward gender equality and women’s empowerment. In particular, the brief summarizes work from a portfolio of six PIM co-funded projects (2020–2021) on gender dynamics in value chains beyond the production node and single commodity analysis (Box 1), a book chapter in a CGIAR-wide gender publication (Pyburn and van Eerdewijk 2021), the Pro-WEAI (project-level Women’s Empowerment in Agriculture Index) for Market Inclusion, and other gender-integrated value chain work within PIM (Crimi 2018; Vos and Pyburn 2021), and provides an outlook for future research.